Antecedents and outcomes of nonprofit public service motivation in Korean NPOs. Issue 5 (1st August 2016) - Park, Sung Min; Kim, Min Young
Abstract : Purpose: This study investigated the role of NPSM as a cognitive dimension in the enhancement of managerial accountability of Korean NGO employees. Hypotheses and a research model were designed to determine the antecedent and consequence factors of NPSM from the perspective of the self-determinants theory, social learning theory, and social exchange theory. Design/methodology/approach: This study relies on quantitative data obtained from Korean NGO survey questionnaires. The sample consists of 400 employees working for NGOs. The performance evaluations were conducted within a one-year period. Findings: Results of the study demonstrate that training and development are the keys to leading employees' value congruence and motivation. We also confirmed that P-O fit is directly associated with NPSM. Finally, intrinsically motivated NGO employees would boost the level of managerial accountability among the Korean NGO employees through organization and socialization. Research limitations/implications: Through applying Perry's original PSM scale including rational, normative, and affective values, the EFA and CFA results confirmed that the constructs of NPSM were valid and reliable in the Korean NGOs. Additionally, it might also explain the locus of causality of SDT, and how it changes people's motivation . Finally, we confirmed that organizational systems are notable in terms of increasing P-O fit, strengthening intrinsic motivation, and increasing organizational consequences. Practical implications: This study confirms that HRD practices and PMS act as very effective managerial tools for nurturing positive and constructive social exchange relationships between organizational constituents, and for developing human resources in the NGOs. This is evident in cases of individuals being given extensive participation rights when it comes to decision-making (Leana et al, 1992; Mayer & Schoorman 1998). The benefit of this reality is twofold: it strengthens individuals' perceptions of self, fostering intrinsic motivation, and it also acts as a buffer of sorts between individuals and external pressures, weakening extrinsic motivation. Originality/value: Given that most Korean NPOs are very small and lack formal HR departments or functions, it is possible that this lack of formality has been somewhat responsible for the shortage of research on the outstanding aspects and issues surrounding nonprofit HR management and the motivation of nonprofit employees. However, as the nonprofit sector has become more professionalized and specialized in terms of training, development, and identity, the need to understand HR issues and employee motivation is vital to improve both employee management and organizational strategies. The aim of this research is to further the understanding of what makes the nonprofit workforce distinct. We believe that the similarities in terms of motivation for public and nonprofit employees allowed us to use a modified version of Perry's (1996) scale in our study to examine NPSM. However, drawing on these various and diverse perspectives on PSM and NPSM, especially in the Korean context, we define NPSM as "intrinsically and voluntarily driven attitudes and dispositions that lead to more service delivery, fund-raising, and volunteering activities in the nonprofit agencies."